Unprecedented five-fold interpenetrated donor–acceptor hybrid heterostructure induced by anion–π interactions. Issue 44 (21st October 2019) - You, Ming-Hua; Li, Meng-Hua; Liu, Yong-Fei; Li, Hao-Hong; Lin, Mei-Jin
Abstract : An unprecedented five-fold interpenetrated D–A hybrid heterostructural complex has been constructed, wherein anion–π interactions play a key role in its interpenetration and photoinduced electron transfers. Abstract : The combination of hexacyanoferrate anions with protonated N, N ′-dipyridyl-naphthalene diimide tectons resulted in a novel cuboid 3-D H-bonded anion-coordinated framework. Induced by anion–π interactions, such a unique framework is further catenated into an unprecedented five-fold interpenetrated D–A hybrid heterostructure with 1-D hexacyanoferrate polyanions and naphthalene diimide aggregates as electron donors and acceptors, respectively. The photophysical and photochemical properties have also been discussed.